Global Trends and Action Items for the Prevention and Control of Emerging and Re-Emerging Infectious Diseases - Silvia De Gaetano; Elena Ponzo; Angelina Midiri; Giuseppe Mancuso; Daniele Filippone; Giovanni Infortuna; Sebastiana Zummo; Carmelo Biondo (Hygiene, 2025)
In recent decades, the world has observed the emergence and re-emergence of a multitude of previously non-existent or re-emerging infectious diseases, for which there is a paucity of timely and effective preventative measures. The WHO has published a catalogue of priority pathogens that are likely to trigger future epidemics, with the objective of designing effective prophylactic and therapeutic interventions. The rationale behind these interventions is rooted in a comprehensive understanding of the aetiology, epidemiology, and pathogenesis of the target diseases. While it is imperative to acknowledge the pivotal role that evolutionary changes in pathogens play, it is equally important to recognise the influence of a multifaceted interplay of factors on the emergence and re-emergence of infectious diseases. These include changes in human populations, the vectors and reservoirs of exposure, and environmental changes. This review summarises the aetiology, epidemiology, and pathogenesis of the ten WHO priority diseases, as well as those with high epidemic potential that are already the focus of specific control programme initiatives, such as HIV/AIDS, tuberculosis, and malaria diseases. Furthermore, this review concentrated on the means of addressing these infections through public health surveillance and response systems. Such systems must be designed to rapidly detect unusual and unexpected disease patterns, track and share information in real time, and rapidly mobilise global responses, which are the most important ways to effectively contain transmission.